The Effect of Gamal Leaf (Gliricidia sepium (Jacq.) Kunth ex Walp)-based Liquid Organic Fertilizer on The Vegetative Growth of Lettuce (Lactuca sativa L.) - Nisa, Chairul; Idris, M; Rahmadina (SCISCITATIO, 2024)
The growth of lettuce depends on the interaction of growth and environmental conditions. Improper crop maintenance may cause low yield of lettuce production. Application of liquid organic fertilizer could be performed as a strategy in crop maintenance. This study aimed to determine the effect and concentration of gamal leaf (Gliricidia sepium (Jacq.) Kunth ex Walp)-based liquid organic fertilizer (LOF) on the vegetative growth of green lettuce plants (Lactuca sativa L.). The research method used a non-factorial Randomised Group Design (RGD), with treatments consisted of P0 (control), P1 (20% gamal leaves-based LOF), P2 (40% gamal leaves-based LOF), and P3 (60% gamal leaves-based LOF). The results showed that Gamal leaves-based liquid organic fertilizer (LOF) that is produced in this research might still contain less macronutrients C, N, P and K that is stated by SNI 7763: 2018 (2-6%), but its application on lettuce as tested plants could still support their growth. Dose of P1 (20%) was the best to support lettuce growth in the form of increased plant height and leaf area index. Dose of P2 (40%) was abble to maintain showed minimum decrease on lettuce total chlorophylls content. Application of dose of P2 (40%) on lettuce growth medium supportes highest uptake of N while the application of dose of P3 (60%) showed highest uptake of P.